Pelaksanaan Pembelajaran Terpadu Tingkat Sekolah Dasar Di Sekolah Dasar Negeri 02 Bumiharjo Waykanan - Syamsiani Syamsiani (El-Idare, 2022)
This study aims to determine how the implementation of integrated learning at the elementary school level at SDN 02 Bumiharjo. The problems that occur are related to the implementation of integrated learning at the elementary school level, because the implementation at the elementary school level requires the right strategy so that this integrated learning can run well. In this research, the type of research used is the type of field research that is qualitative. In the study, informants were also the head of the library, educators and education staff, as well as students and other stakeholders related to this article. Data collection techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the discussion, it can be concluded that integrated learning as a learning strategy based on an integrated curriculum approach that aims to create or create a relevant learning process, with principles including the principle of extracting themes, the principle of implementing integrated learning, the principle of evaluation and the principle of reaction and meaningful for children so that they have an important role at the elementary school level in accordance with the development of the children's age. The implementation has been going well and the implementation consists of three forms of implementation, namely the implementation that is carried out spontaneously, the implementation in the form of an integrated day, and the implementation that starts from the theme.